Factors Related to the Implementation of the Covid-19 Vaccine in the Indonesian Army in District-City, Riau Province - Yalesvitri Yalesvitri; Ennimay Ennimay; Aldiga Rienarti Abidin; Budi Hartono; Hetty Ismainar (Institute of Computer Science (IOCS), 2022)
The Indonesian Armed Forces synergizes with the government to accelerate the implementation of the COVID-19 vaccination. Objectives, knowing the factors related to the achievement of the implementation of the COVID-19 vaccine invasion of the Indonesian Army.Method, using a quantitative method with a cross-sectional study approach. The sampling method was accidental sampling. The number of respondents was 96 community respondents and 16 respondents from the vaccination team. Data was collected using questionnaires and observations. Data were analyzed using Chi Square test statistical software. Result,there is a relationship between knowledge and public perception < 0.05, the value of = 0.009, not good with the achievement of vaccine 1 (20%), vaccine 2 (14.5%), vaccine 3 (65.5%). The unrelated factors are the knowledge and skills of the vaccination implementation team > 0.05, the value of = 0.006, the type of vaccine available > 0.05, the value of = 0.585), the COVID-19 vaccine distribution system > 0.05, the value of = 0.359 and facilities and infrastructure > 0.05 the value of = 0.854. The relationship between incentive motivation of the vaccination team and the achievement of vaccine implementation was not good (43.8%) and good (56.3%). Vaccination achievements in the four Military District with good category 70.8%, quite good 17.7% and not good 11.5%. Conclusion, the related factors are knowledge and public perception about the COVID-19 vaccine with the achievement of the implementation of the incursion COVID-19 vaccine. The Army while unrelated factors include the knowledge and skills of the vaccination team, the types of vaccines available, the COVID-19 vaccine distribution system and facilities and infrastructure.